The implications of ethnic division in Afghanistan, with particular reference to the Hazara Mongols - Jones, SA (1976)
The study of Afghanistan has been more limited than that of other areas of the Moslem world. Afghanistan tends to fall outside the neat categories of Middle East, South Asia or Central Asia, utilised by historians and social scientists. Indeed, up until the nineteenth century, the area was only rarely penetrated by western travellers or scholars and many were hampered in their investigations by a hostile or inaccessible situation. The accounts of this period were often written by European army officers or travellers and such sources, some of which have been used in the present study, need to be read with caution. An awareness of the writer's backgrounds, training and motives is important, because some reports are biased and perhaps not as reliable as one would wish. A more accurate picture of this period could possibly be obtained by consulting archives in Kabul, and it is hoped that this will be carried out at a future date. With the increase of foreign political and economic influence in the area, Afghanistan in the twentieth century has been more open to Western ethnographers and other social scientists. These have been mainly American, Russian, German, French and Danish and the Central Asian Research Centre in London has assisted researchers in collecting and translating various works. However, our general anthropological knowledge of this area remains limited and it is notable that women anthropologists have undertaken little study in Afghanistan. The present study is not based on fieldwork and therefore attempts to examine one ethnic group in Afghanistan with the help of library materials available in Britain. The Hazaras are a minority ethnic group, with a history of slavery and oppression, who have attracted the attention of foreign ethnographers because of their supposed Mongol descent. They are the main religious heterodox group in Afghanistan and this fact appears to have considerable importance in their relationship with the ruling Pashtuns. Accordingly I have attempted here to outline some of the main features of ethnic relations in Afghanistan, concentrating particularly on the Hazara-Pashtun relationship as it has developed or changed in the last hundred years. This discussion may indicate general directions for the analysis of ethnicity and the ethnic group. Sources for this thesis were found in two main areas. Firstly secondary sources on Afghanistan in recent years were available in libraries in Oxford and London. These were mainly English and American, thus omitting much possibly relevant Russian material, although some Russian articles in translation were available from the Central Asian Research Centre. Primary sources and rare volumes were consulted at the India Office archives, which forms a valuable repository for information received through British sources in India and Afghanistan. Chapter One of the thesis provides an introduction to Afghan society, outlining the contemporary environmental and social divisions. In Chapter Two, recent ethnography is utilised to present a description of Hazara society of the last thirty years. Chapter Three takes the historical viewpoint of discussing the various theories of Hazara ethnogenesis and also describes the state of Hazara society in the nineteenth century, when the forces of European imperialism and Afghan nationalism were already beginning to impinge on the isolation of the Hazaras and to effect changes in ethnic relations. The fourth chapter suggests certain results of these changes; the Hazara resistance to the rise of the Sunni state and the way in which sectarian allegiances were mobilised as political forces. One particular area where ethic relations have been crucial in an economic and possibly political sense is in the relationship between the sedentary Hazaras and the Pashtun nomads, and this is discussed in Chapter Five. Chapter six finally attempts to review these developments described, in the light of contemporary theories of ethnicity. Further research and fieldwork would enable a more definitive anthropological study to be undertaken, but the present study limits itself to describing the changes in ethnic relations and suggesting points for more detailed investigation.